Development of the fire-retardant sandwich structure using an aramid/glass hybrid composite and a phenolic foam-filled honeycomb. (15th December 2016) - Kim, Minkook; Choe, Jaeheon; Lee, Dai Gil
Abstract: Sandwich structures are increasingly used in high-performance engineering application because of their high specific stiffness, strength, environmental resistance and thermal insulation characteristics. However, poor fire resistance is a critical problem for the use of sandwich structures in engineering applications. In this study, a fire-retardant sandwich structure was developed using a phenolic foam filled honeycomb and carbonized phenolic matrix aramid/glass hybrid composite faces. The sandwich structure was designed to satisfy the limit of critical thermal radiation to humans. To improve the post-fire properties and fire resistance of the glass/phenolic composite, a phenolic coating and an aramid/phenolic composite layer were applied on the surface. The carbonization and impregnation of the phenolic matrix of the composite were repeated twice to eliminate the matrix cracking and delamination by fire exposure. Phenolic foam-filled honeycomb core was used to reduce the thermal conductivity and increase the stiffness and strength of the sandwich. Finally, the thermal insulation and post-fire flexural properties of the sandwich structure were estimated.